2005
DOI: 10.1097/01.ccm.0000150741.12906.bd
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in sepsis survivors from cecal ligation and perforation*

Abstract: Our data provide the first experimental demonstration that survivors from CLP show learning and memory impairment after complete physical recovery from sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
3
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(73 citation statements)
references
References 9 publications
3
63
3
3
Order By: Relevance
“…The animals were subjected to CLP as previously described (19)(20)(21)(22). Briefly, rats were anesthetized with a mixture of ketamine (80 mg/kg) and xylazine (10 mg/kg), given intraperitoneally.…”
Section: Cecal Ligation and Perforation Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…The animals were subjected to CLP as previously described (19)(20)(21)(22). Briefly, rats were anesthetized with a mixture of ketamine (80 mg/kg) and xylazine (10 mg/kg), given intraperitoneally.…”
Section: Cecal Ligation and Perforation Surgerymentioning
confidence: 99%
“…Shimizu et al (23) demonstrated that 24 h after CLP animals presented learning impairment in passive avoidance retention. Moreover, we recently reported that CLP-induced sepsis survivors presented learning, aversive and spatial memory impairment when submitted to behavioral tasks 10 days after CLP (21) and learning and aversive memory impairment lasting up to 30 days after CPL (22). Thus, CLP seems to be a good model for the study of cognitive and emotional alterations as late manifestation of sepsis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(43,44) Acute encephalopathy has demonstrated in animal models of polymicrobial sepsis, and human sepsis survivors present cognitive impairment that could be a secondary effect of CNS damage. (26) In addition, survivors from critical care units, including sepsis patients, may show persistent brain-related morbidity, including neurocognitive deficits and development of psychiatric disorders. (45)(46)(47)(48)(49) In the present study, we demonstrate that citrate synthase activity is inhibited in the prefrontal cortex and cerebral cortex of adult rats after sepsis induced by CLP.…”
Section: Discussionmentioning
confidence: 99%
“…All animals showed signs of encephalopathy at 6 h after sepsis (lethargy, mild ataxia, lack of spontaneous movement, and loss of righting reflex) and gradually returned to their normal waking status 24-36 h after CLP. (26) To minimize the possibility of animals not developing sepsis, the CLP procedure was always performed by the same investigators. In addition, all animals were observed after CLP to determine signs of infection (pyloerection, lethargy, tachypnoea and weight loss), and the number of animals that survived is in accordance with our previous reports.…”
Section: Cecal Ligation and Perforation Surgerymentioning
confidence: 99%